Se déplacer en voiture à Boston : essai de mesure de circulation en temps réel par usage des floating car data (données flottantes automobiles) - Gérald Billard; Alain Wrobel (Netcom)
How could we measure the real car travel time in the US metropolitan areas? After introducing the context of urban planning and the new issues of mobility in the United States, this paper will present a new methodology developed to measure the accessibility of a given place. This original method uses real time data extracted from the TomTom website.